Thomas Pynchon’s Against the Day: A Deleuzian Reading of Pynchon’s Language - Salami, Ali; RAHMANI, Razieh (Anafora, 2023)
This study explores Pynchon’s mammoth novel, Against the Day, in terms of the minor practice of language as proposed by Deleuze and Guattari in their book Kafka: Toward a Minor Literature, which opens up new possibilities for literary criticism. With his idiosyncratic, intensive, and inventive practice of language, Pynchon shatters the already existing notions of appropriate and homogenizing forms of major language. The novel demystifies the language’s institutionalized system of signification and defies identifiable decipherable meaning in many ways, such as covert and overt deterritorialization of language, escape from “territorial” and “representational” language, defiance of signification, neutralization of sense, asyntactical language, phantasmagorical and absurd tales, quizzical jokes, silly songs, and asubjective free indirect narration. Against the Day’s practice of language prefers the territory of asubjective insignification to subjective, symbolic, and signifying usage of language so as to dismantle the territory of representation; thus, it pushes the major language towards or even out of its limits.